1988
DOI: 10.1002/em.2860120408
|View full text |Cite
|
Sign up to set email alerts
|

Nitrilotriacetic acid (NTA) induces aneuploidy in drosophila and mouse germ‐line cells

Abstract: The ability of nitrilotriacetic acid (NTA) to induce aneuploidy was studied in the germ line of both Drosophilu and the mouse. The Free Inverted X Chromosomes (FIX) genetic system, adopting a brooding scheme, was used to detect induced aneuploidy in Drosophil~, and a cytogenetic method based on chromosomal counting in secondary spermatocytes was used in the mouse.In Drosophilu a highly significant (P < 0.001) increase of aneuploidies was produced by NTA (5 X M), which was greater than that produced by colchici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The results obtained in Drosophila and the mouse with two chelating agents, NTA and EDTA [Costa et al, 1988;Russo et al, 1989;Zordan et al, 1990;present study] were encouraging for a reciprocal validation of the aneuploidy assays available for these organisms. Not only we observed that each compound acts with the same modality [chromosomal gain for NTA, Costa et al, 1988; chromosomal loss for EDTA, Zordan et al, 1990, and present results] on different eukaryotic test systems, but we also noticed, at least as far as EDTA is concerned, a different response of somatic with respect to germ cells both in Drosophila and the mouse [Zordan et al, 1990, and present results, Fig. 11. This recurrence is suggestive, even taking into consideration some limits, such as the lack of a complete dose-effect relationship for MN induction by EDTA in mouse cells, or the not perfect endpoint overlapping of the somatic and germ tests in Drosophila.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results obtained in Drosophila and the mouse with two chelating agents, NTA and EDTA [Costa et al, 1988;Russo et al, 1989;Zordan et al, 1990;present study] were encouraging for a reciprocal validation of the aneuploidy assays available for these organisms. Not only we observed that each compound acts with the same modality [chromosomal gain for NTA, Costa et al, 1988; chromosomal loss for EDTA, Zordan et al, 1990, and present results] on different eukaryotic test systems, but we also noticed, at least as far as EDTA is concerned, a different response of somatic with respect to germ cells both in Drosophila and the mouse [Zordan et al, 1990, and present results, Fig. 11. This recurrence is suggestive, even taking into consideration some limits, such as the lack of a complete dose-effect relationship for MN induction by EDTA in mouse cells, or the not perfect endpoint overlapping of the somatic and germ tests in Drosophila.…”
Section: Discussionmentioning
confidence: 95%
“…This recurrence is suggestive, even taking into consideration some limits, such as the lack of a complete dose-effect relationship for MN induction by EDTA in mouse cells, or the not perfect endpoint overlapping of the somatic and germ tests in Drosophila. Also in previous experiments with NTA, the ability of this chelating agent to induce aneuploidy in the mouse was specifically referred to the germ cells [Costa et al, 1988;Russo et al, 19891. These results confirm that the enrichment of a specific data base for germinal effects of chemicals present in the environment is an urgent goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybridization data of Table 1 were used to calculate an overall sperm aneuploidy frequency for comparison with these literature values. By Beatty et al, 1975Miller and Adler, 1992Brook and Chandley, 1986Liang et al, 1986Liang and Pacchierotti, 1988 Liang Hunt, 1987Costa et al, 1988Zordan et al, 1990Pacchierotti et al, 1987Risley et al, 1990Risley et al, 1990 Maudlin we obtained a n average per-chromosome frequency of 2.9 hyperhaploid spermatids per 10,000. Multiplying this frequency by the number of mouse chromosomes and by a factor of 2 (to account for an equal number of hyperhaploid and hypohaploid cells), we obtained an overall frequency of sperm aneuploidy of 1.16.…”
Section: Resultsmentioning
confidence: 92%
“…This weak effect may be compared to the results obtained by Bora [1975] which related a significantly high frequency of tetraploïd cells and endoreplication in human lymphocytes after very long treatments and to the results presented by Modesti et al [1995] which showed that NTA interacted with tubulin in vitro in mammalian cells. Furthermore, NTA was shown to be able to induce in vivo aneuploidy in Drosophila and mouse germ-line cells [Costa et al, 1988] and mitotic recombination and possible aneuploidy in somatic cells of Drosophila [Zordan et al, 1991].…”
Section: Discussionmentioning
confidence: 98%